Assessment of Proximate, Vitamins, In Vitro Antioxidant, and Functional Properties of Some Polyherbal Formulations as Prospective Botanical Candidates for Pharmaceutical Applications - Abubakar Mannir Rawayau; Aliyu Sani Yandoma; F Lawal Muhammad; Nasir Rufa'i; Ahmed Sani; A Halliru (UMYU Journal of Microbiology Research, 2024)
Study’s Novelty/Excerpt